THREE INVISIBLE HANDS: COMMENTS ON THE PLENARY PRESENTATIONS AT THE DSA CONFERENCE 2008 BY PAST PRESIDENTS PAUL MOSLEY, FRANCES STEWART, JOHN TOYE-AND THE ESSAY BY PAST PRESIDENT JOHN HARRISS - Harriss-White, B (2009)
Responding to three plenary addresses at the DSA conference 2008, and another written contribution, this paper comments on the invisible hand; the dynamics of institutional change; the role of the (commodified) state; 'markets' versus actually existing capitalism and the implications of global warming for development studies. © 2009 John Wiley and Sons, Ltd.